How does carrageenan cause colitis? A review. (15th February 2023) - Guo, Juanjuan; Shang, Xuke; Chen, Peilin; Huang, Xiaozhou
Abstract: Carrageenan is a common additive, but mounting studies have reported that it may cause or aggravate inflammation in the intestines. The safety of carrageenan remains controversial and its inflammatory mechanisms are unclear. In this review, the pathogenesis of colitis by carrageenans was discussed. We analyzed the pathogenesis of inflammatory bowel disease, followed that line of thought, the existing evidence of carrageenans causing colitis in cellular and animal models was summarized to draw its colitis pathogenesis. Two pathways were described including: 1) carrageenan changed the composition of intestinal microbiota, especially Akkermansia muciniphila, which destroyed the mucosal barrier and triggered the inflammatory immune response; and 2) carrageenan directly contacted with receptors on epithelial cells and activated the NF-κB inflammatory pathway. This review aim to provide guidance for exploring the treatment of colitis caused by carrageenan, and safe processing and utilization of carrageenan in food industry, which is worthy of study in the future. Graphical abstract: Unlabelled Image